2017
DOI: 10.1371/journal.pone.0169939
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Cholesterol Esterification in Plasma of apoc2 Knockout Zebrafish and Familial Chylomicronemia Patients

Abstract: Hypertriglyceridemia is an independent risk factor for cardiovascular disease. Apolipoprotein C-II (APOC2) is an obligatory cofactor for lipoprotein lipase (LPL), the major enzyme catalyzing plasma triglyceride hydrolysis. We have created an apoc2 knockout zebrafish model, which mimics the familial chylomicronemia syndrome (FCS) in human patients with a defect in the APOC2 or LPL gene. In this study, we measured plasma levels of free cholesterol (FC) and cholesterol esters (CE) and found that apoc2 mutant zebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…All major classes of apolipoproteins (ApoA, ApoB, ApoC, and ApoE) are expressed in zebrafish and are highly similar to human apolipoproteins (79). As mentioned above, hypertriglyceridemia is an independent CVD risk factor caused by single mutations in the genes encoding lipoprotein lipase (LPL) or in those encoding LPL cofactors, such as APOC2 (28,55). Liu et al demonstrated that apoc2 −/− zebrafish exhibit properties of human patients, including dyslipidemia, specifically hypertriglyceridemia as early as 14 dpf, which resulted in type II atherosclerosis.…”
Section: Zebrafishmentioning
confidence: 99%
“…All major classes of apolipoproteins (ApoA, ApoB, ApoC, and ApoE) are expressed in zebrafish and are highly similar to human apolipoproteins (79). As mentioned above, hypertriglyceridemia is an independent CVD risk factor caused by single mutations in the genes encoding lipoprotein lipase (LPL) or in those encoding LPL cofactors, such as APOC2 (28,55). Liu et al demonstrated that apoc2 −/− zebrafish exhibit properties of human patients, including dyslipidemia, specifically hypertriglyceridemia as early as 14 dpf, which resulted in type II atherosclerosis.…”
Section: Zebrafishmentioning
confidence: 99%
“…Recently, deficient cholesterol esterification has been found to occur in an apoC11-deficient zebrafish, which mimics the familial chylomicronemia syndrome in human patients, with a defect in apoC2 or LpL genes. 115 ApoC111 inhibits the delipidation of triglyceride from the particle by inhibiting the action of LpL, thus delaying the clearance of the particle from the circulation. 116 The Bruneck Study 117 was designed to examine the importance of various apolipoproteins in the genesis of cardiovascular events over a 10-year period.…”
Section: Triglyceride and Cholesterol Absorption In Diabetesmentioning
confidence: 99%
“…Similar to mammals, microsomal triglycerides transfer protein play a critical role in lipid transport in zebrafish [ 14 ]. The zebrafish also express cholesteryl ester transfer protein (CETP) and are susceptible to atherosclerosis, making them attractive models for studying this disorder [ 15 ]. Apart from these physiological similarities, zebrafish also possess orthologues of critical lipid metabolic genes including microsomal TG transfer protein ( mttp ), fatty acid transport protein ( slc27a ), and acyl-CoA synthetase ( acsl ) gene families, as well as the LDL receptor ( ldlr ).…”
Section: Introductionmentioning
confidence: 99%